A Review of Some Methods used for Drought Identification and Analysis - J.F, Agwata (Africa Environmental Review Journal, 2022)
Water management under extreme hydrologic conditions such as drought is a challenging issue to hydrologists, engineers and environmental scientists. To ensure sustainable management of water during drought periods and to adequately resolve various issues related to drought occurrence and management at various scales, it is important that suitable methods and procedures for drought identification and analysis be known. Examining the available techniques can do this. In this paper, some of the methods that can be used to identify and analyse drought are reviewed. Although several methods are available for drought identification and analysis, it is noted that not a single technique can be used for all drought types and in all circumstances and that for various drought types, it is necessary that they be identified and analysed using a combination of different techniques.